2020
DOI: 10.1111/ibi.12829
|View full text |Cite
|
Sign up to set email alerts
|

Circannual variation in habitat use of the White‐winged SnowfinchMontifringilla nivalis nivalis

Abstract: High mountain areas are subject to strong seasonal fluctuations, and species inhabiting these particular environments show a high degree of habitat specialization to cope with extreme abiotic conditions. Estimates of habitat use are influenced by the spatial and seasonal scales at which they are evaluated, so studies at multiple scales are important in order to explore adaptive responses to seasonal environments. In the present study, we assessed habitat use of the White‐winged Snowfinch Montifringilla nivalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Many alpine species are adapted to cope with the harsh environmental conditions typically found at high elevations (Bettega et al, 2020; Cheviron & Brumfield, 2012; Lu et al, 2009). Because of their tight link with such conditions, these species may be particularly vulnerable to environmental changes, which could dramatically impact their populations (Martin & Wiebe, 2004; Tingley et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many alpine species are adapted to cope with the harsh environmental conditions typically found at high elevations (Bettega et al, 2020; Cheviron & Brumfield, 2012; Lu et al, 2009). Because of their tight link with such conditions, these species may be particularly vulnerable to environmental changes, which could dramatically impact their populations (Martin & Wiebe, 2004; Tingley et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, in autumn and winter, they exclusively feed on seeds of alpine plants [50]. Depending on the amount of snow cover, feeding grounds in winter are fairly unpredictable and are patchily and heterogeneously distributed [39]. Foraging in large groups may benefit snowfinches when moving in a quite nomadic manner to locate prime feeding grounds of alpine forbs or shrubs that need to be exposed to be accessible.…”
Section: Discussionmentioning
confidence: 99%
“…From 1990 to 2013, 10 843 observations on snowfinches were collected in Switzerland, Italy and Spain, in the framework of different studies carried out by the authors [39][40][41][42] and by national parks and local institutions. In addition, data collected by the public (citizen science) and gathered through online databases (www.ornitho.at, www.ornitho.ch, www.ornitho.it, www.…”
Section: Materials and Methods (A) Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is striking evidence that white‐winged snowfinches are strictly associated with cold alpine environments, in terms of their distribution (Brambilla et al 2017a, 2020, Brambilla and Delgado 2020, BirdLife International 2021, de Gabriel Hernando et al 2021), foraging areas (Antor et al 1995, Brambilla et al 2017b, 2018), social behaviour (Delgado et al 2021), survival rates (Strinella et al 2020) and habitat and nest‐site selection (Heiniger 1991a, b1991b, Brambilla et al 2017b, Bettega et al 2020, Niffenegger 2021). The dependence of this species on cold environments is particularly strong during the breeding season (Brambilla et al 2019, 2017a, Resano‐Mayor et al 2019, Schano et al 2021, Alessandrini et al 2022, de Gabriel Hernando et al 2022): the breeding distribution of the species in European mountains is associated with low values of annual average temperature (Brambilla et al 2017a, 2020, 2017a, de Gabriel Hernando et al 2021), suggesting a thermal niche much narrower than that suggested by Cobos et al (2021).…”
Section: A Worked Example: the Thermal Niche Of The White‐winged Snow...mentioning
confidence: 99%